2016
DOI: 10.1016/j.energy.2016.04.073
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic performance of a novel offshore power system integrated with a wind farm

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Another challenge that arises from this standard solution is the grid stability for large wind installed capacity. For example, Orlandini et al (2016) showed that a maximum wind power of 10 MW was feasible considering an installed electrical load of 30 MW to comply with frequency requirements. Conservative operating strategies are often applied to achieve the requested level of reliability and flexibility, leading to poor performance and increased emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge that arises from this standard solution is the grid stability for large wind installed capacity. For example, Orlandini et al (2016) showed that a maximum wind power of 10 MW was feasible considering an installed electrical load of 30 MW to comply with frequency requirements. Conservative operating strategies are often applied to achieve the requested level of reliability and flexibility, leading to poor performance and increased emissions.…”
Section: Introductionmentioning
confidence: 99%
“…CCS could also allow a concept involving offshore production of clean power from gas and export of the surplus to the mainland to help decarbonise mainland electricity [19]. Alternatively, the integration of wind power to either simple cycle gas turbines [20] or combined cycles [21,22] could contribute to cut CO 2 emissions, though not to eliminate them as a conventional power generator is still needed to provide base load and heat to the processes. The integration of renewable sources could as well be a far-sighted option as it could allow reconverting the oil & gas installations into renewable energy production sites [23].…”
Section: Introductionmentioning
confidence: 99%
“…Even though a couple of co-generative solutions were discussed, the necessity to supply heat in parallel to power was not simulated in detail. In a follow-up paper [17], an economic analysis was proposed, comparing the economic performance of the wind farm coupled with three combined cycles to that of the wind farm coupled with three gas turbines. The results showed that the first concept (wind power and combined cycle) becomes more convenient when fuel cost increases or when the CO 2 tax increase.…”
Section: Introductionmentioning
confidence: 99%